Development of regiocontrolled pentadienyl indium condensations and a carbometallation-intramolecular cycloaddition synthesis of taxoids - Villalva, Nidia (University of Ottawa (Canada), 2003)
The synthesis of the taxanes derivatives has been the major focus of this research. The efforts made towards the synthesis of these complex and successful drugs for the treatment of cancer have resulted in the development of efficient synthetic strategies. These approaches have arisen mainly from our studies in the carbometallation of propargyl alcohols and the development of stereoselective Lewis acid catalyzed IMDA. The application of these potential synthetic strategies has yielded very significant results. The synthesis of the tricyclic core of the taxanes (2.149) by a novel carbometallation-cycloaddition-RCM sequence was successfully achieved using readily available starting materials and mild reaction conditions. In addition, the versatile carbometallation-cycloaddition sequence allowed the synthesis of AB ring system of taxanes with different functionalities (2.126, 2.111 and 2.128). The construction of a functionalized A ring (2.84) was also accomplished. This intermediate and some of its derivatives were employed to attempt the synthesis of B ring of taxanes by RCM. Additionally, the further functionalization of AB and ABC ring-systems of taxanes was investigated. Unfortunately, the synthesis of a biological active taxane derivative was not possible. In addition, we have studied the in situ carbonyl addition oxy-Cope rearrangement of unsaturated ketones.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, General.; Chemistry, Pharmaceutical.